2014
DOI: 10.1017/s0007114514003419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psyllium on LDL-cholesterol concentrations in Brazilian children and adolescents: a randomised, placebo-controlled, parallel clinical trial

Abstract: The present study investigated the LDL-cholesterol (LDL-C)-lowering effects of psyllium in Brazilian dyslipidaemic children and adolescents. A total of fifty-one individuals (6 -19 years) with mild-to-moderate hypercholesterolaemia were evaluated by conducting a randomised, double-blind, placebo-controlled, parallel clinical trial. Over an 8-week trial period, the participants were randomly allocated to one of two groups (control: n 25 and psyllium: n 26) using a computer-generated random number sequence. Fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…1). It has already been shown that long-term PSH consumption prevents MI by blocking the preocclusion steps, because PSH consumption was effective in reducing risk factors for coronary ischemic disease such as hyperlipidemia [1112], diabetes [14], and hypertension [15], which promote the formation of atherosclerotic plaques responsible for narrowing the coronary arteries (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). It has already been shown that long-term PSH consumption prevents MI by blocking the preocclusion steps, because PSH consumption was effective in reducing risk factors for coronary ischemic disease such as hyperlipidemia [1112], diabetes [14], and hypertension [15], which promote the formation of atherosclerotic plaques responsible for narrowing the coronary arteries (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this is a slow process and usually takes several decades [10]. Previous studies have demonstrated the efficacy of psyllium seed husk (PSH) consumption in reducing risk factors such as hyperlipidemia [11,12,13], diabetes [14], and hypertension [1516], thereby inhibiting the preocclusion steps (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Following an average intake of psyllium of 10 g/day, an average reduction of LDL-C of 7% was observed [59]. Moreover, psyllium showed good efficacy also in children and adolescents, with the percentage of LDL-C reduction similar to the one in adults [60]. The reduction of cholesterol was more pronounced in American subjects with hypercholesterolemia, who consumed a high-fat diet (LDL-C -8/20%) [61].…”
Section: Psylliummentioning
confidence: 96%
“…7,31 Only gel-forming fiber supplements (eg, highmolecular-weight b-glucan, raw guar gum, and psyllium), consumed with meals to coincide with bile release, have the requisite high viscosity to effectively lower elevated serum cholesterol concentrations. 7,26,28,[31][32][33] It is important to note that not all viscous fibers can effectively lower elevated serum cholesterol concentrations. A placebo-controlled, randomized, parallel study (105 patients with hypercholesterolemia) assessed the cholesterollowering effects of psyllium (a natural gel-forming fiber) vs methylcellulose (a semisynthetic viscous soluble fiber made from wood pulp) and polycarbophil (a synthetic polymer).…”
Section: Misconception #1: All Soluble Fibers Lower Elevated Serum Chmentioning
confidence: 99%